The relationship between resource dependency and market orientation : the specific case of non-profit organisations (NPOs) - Macedo, Isabel Maria (2004)
In the context of an increasingly competitive environment in which organisations are compelled to manage their resources and capabilities in more efficient and effective ways, the concept of market orientation has been acknowledged as highly important in the marketing and management literature. The existing literature, however, has mainly been focused on the for-profit sector and, to our best knowledge, little research has been undertaken in other organisational contexts, such as the non-profit sector. Given the specificity of NPOs and the increasingly demanding resource environments in which these organisations operate, the present study examines the extent to which resource dependence impacts the market orientation construct. The results of the first cross-sectional study on the market orientation of Portuguese NPOs are reported.